Effect of vitexin on Aspergillus fumigatus keratitis in mice and its mechanism - XU Haining, YI Wendan, JIA Yiyi, LI Cui, YIN Min, GU Lingwen, ZHAO Guiqiu (精准医学杂志)
Objective To investigate the protective effect of vitexin against Aspergillus fumigatus (A. fumigatus) ke-ratitis in mice and its mechanism. Methods The effect of vitexin on the survival rate of human corneal epithelial cells (HCECs) and RAW264.7 cells was evaluated using Cell Counting Kit-8. Mice were divided into three groups: control group, A. fumigatus keratitis group, and vitexin-treated group (10 μL of 100 mg/L vitexin was injected subconjunctivally once a day for 3 consecutive days). The severity of fungal keratitis (FK) was evaluated using clinical scores. Hematoxylin-eosin staining was used to detect the inflammatory cell infiltration in the mice. Plate counting was used to determine corneal fungal load in the mice. Changes in the mRNA expression levels of IL-1β, IL-6, MIP-2, and LOX-1 in the mice and RAW264.7 cells were measured using quantitative real-time PCR. The expression level of LOX-1 protein in RAW264.7 cells was determined using Western blotting. Results Vitexin did not have a significant effect on the viability of HCECs cells at a concentration lower than 100 mg/L and did not have a significant effect on the viability of RAW264.7 cells at a concentration lower than 150 mg/L. Compared with A. fumigatus keratitis group mice, vitexin-treated mice showed a slower course of keratitis progression, decreased inflammatory cell infiltration in the cornea, and a significantly reduced corneal fungal load (t'=19.27,P<0.05). Meanwhile, the mRNA expression levels of IL-1β, IL-6, MIP-2, and LOX-1 in the vitexin-treated group were significantly reduced compared with those in A. fumigatus keratitis group (t=4.95-6.15,P<0.05). The mRNA expression levels of IL-1β, IL-6, MIP-2, and LOX-1 and the protein expression level of LOX-1 were significantly reduced in vitexin-treated RAW264.7 cells compared with those in hyphae-stimulated cells (t=-64.68-40.02,P<0.05). Conclusion Vitexin has a protective effect on A. fumigatus-stimulated RAW264.7 cells and FK in mice cornea, which may be achieved by downregulating the mRNA expression of IL-1β, IL-6, MIP-2, and LOX-1 and the protein expression of LOX-1 in pattern recognition receptors in RAW264.7 cells and the cornea in mice.